2017
DOI: 10.1038/nsmb.3371
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of the specificity of USP18 toward ISG15

Abstract: Protein modification by ubiquitin and ubiquitin-like modifiers (Ubls) is counteracted by ubiquitin- and Ubl-proteases collectively called DUBs. In contrast to other proteases of the ubiquitin-specific protease (USP) family, USP18 shows no reactivity towards ubiquitin but specifically deconjugates the interferon induced Ubl ISG15. To identify molecular determinants for this specificity, we solved the crystal structures of mouse USP18 and of mouse USP18 in complex with mouse ISG15. USP18 was crystallized in an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
149
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(157 citation statements)
references
References 70 publications
8
149
0
Order By: Relevance
“…Figure 2C shows that the C-lobe residues identified in this analysis cluster on the surface of ISG15, comprising what we will refer to as the “IFN-γ patch” (see also Supplemental Figure S1A). The IFN-γ patch does not correspond to a region that mediates interaction with other known ISG15 binding proteins, including influenza virus NS1B (Guan et al, 2011) or USP18 (Basters et al, 2017), and does not correspond to the “hydrophobic patch” region of ubiquitin, which is the binding site for many ubiquitin binding proteins (Sloper-Mould et al, 2001) (Supplemental Figure S1B, C). …”
Section: Resultsmentioning
confidence: 99%
“…Figure 2C shows that the C-lobe residues identified in this analysis cluster on the surface of ISG15, comprising what we will refer to as the “IFN-γ patch” (see also Supplemental Figure S1A). The IFN-γ patch does not correspond to a region that mediates interaction with other known ISG15 binding proteins, including influenza virus NS1B (Guan et al, 2011) or USP18 (Basters et al, 2017), and does not correspond to the “hydrophobic patch” region of ubiquitin, which is the binding site for many ubiquitin binding proteins (Sloper-Mould et al, 2001) (Supplemental Figure S1B, C). …”
Section: Resultsmentioning
confidence: 99%
“…In ISG15, however, this hydrophobic 'patch' appears to be extended by Trp123 and Pro130, thus allowing His1652 of PLpro to also engage in an interaction. As previously noted by Basters et al for USP18, this region of ISG15 is conserved across different ISG15 species and was proposed to be a unique hydrophobic patch to ISG15 differing from the well-known hydrophobic patch of Ub, which is commonly utilized for recognition by a vast number of Ub-binding proteins (Basters et al, 2017;Komander and Rape, 2012). Our observations and those of others collectively support the hypothesis that this hydrophobic region of ISG15 may be a canonical recognition region that is utilized in general by deISGylases to specifically recognize ISG15.…”
Section: Structural Differences In Recognition Of Isg15 and Ub By Mermentioning
confidence: 85%
“…Trp123 of ISG15 is sandwiched between the aliphatic chain of Arg1649 of PLpro and the hydrophobic side-chain of Val1691, which also interacts with the alkyl group of Thr125 of ISG15. Apart from Thr125, which is unique to human ISG15, the proline and tryptophan residues are conserved among species of ISG15, and appear to be utilized for interactions by a wide range of deISGylases, both in the USP and ovarian tumor family (vOTU), suggesting that this region of PLpro may be critical for ISG15 recognition (Akutsu et al, 2011;Basters et al, 2017;Daczkowski et al, 2017a).…”
Section: Interactions Of Mers-cov Plpro With Isg15mentioning
confidence: 99%
See 1 more Smart Citation
“…Daczkowski et al (2017a) reported that the C-terminal domains of ISG15s (similar to Ub1 mentioned above) from different species have different binding characteristics with SARS-CoV PL2 pro according to two structures, the PL2 pro in complex with the C-terminal domain of hISG15 and mISG15, respectively. In addition, the structure of mouse USP18 in complex with full-length mISG15 became available this year (Basters et al, 2017). Surprisingly, the N-terminal Ubl domain of mISG15 shows almost no interaction with mUSP18.…”
Section: Papain-like Protease 2 (Pl2 Pro )mentioning
confidence: 99%